Critical competence in Active Methodologies: an approach through Mathematical Modelling - Andréa Pavan Perin; Celso Ribeiro Campos (Universidade Federal do Oeste da Bahia, 2020)
Pedagogical proposals should open space for the analysis and reflection of everyday situations. For this to happen, it is necessary that activities are prepared based on Active Methodologies. This article aims to discuss how critical competence was present in a Mathematical Modelling activity carried out with 32 students from the 1st year of high school in a private school from the countryside of São Paulo state. As a methodological path for analysis and validation of the discussions established between students and the teacher, we resort to the qualitative approach, through the analysis of the Collective Subject Discourse. Our analyzes show that critical competence was practiced based on two types of criticism, socio-political and epistemological. Socio-political criticism is characterized by an analysis of social structures (problematic, from their point of view) for the phenomenon studied. The epistemological criticism, on the other hand, refers to the considerations about the built model, considering the procedures, processes and results achieved.